The effect of Benson's sedation on the sleep quality of hospitalized elderly: A randomized controlled trial - Maedeh Sirati; Seyed Amirhossein Pishgooie; Maryam Jadid-Milani (Journal of Nursing Advances in Clinical Sciences)
The present study aims to determine the effect of Benson's sedation on the sleep quality of hospitalized elderly. This experimental study employed a simple random method to assign participants to two test groups of 34 individuals and a control group of 34 individuals. The Pittsburgh Sleep Quality Index (PSQI) was the data collection tool. In the test group, the researcher administered Benson's relaxation technique in four sessions, each lasting 10 minutes, under the supervision of a physician. The control group received only routine interventions. The collected data were analyzed using SPSS version 21, employing descriptive statistics (including tables, means, and standard deviations [SDs]) and inferential statistics (paired t-test and independent t-test). In the experimental group, the mean sleep quality score before the intervention was 9.48 (SD=3.52), which improved to 7.59 (SD=3.17) after the intervention. A paired t-test revealed a significant improvement in sleep quality within this group (P<0.01). In the control group, the mean sleep quality score was 9.21 (SD=3.21) before the intervention and 7.97 (SD=2.89) after the intervention; however, the paired t-test did not show a significant difference (P=0.6). The results of this study indicate that the Benson relaxation technique significantly improved the sleep quality of hospitalized patients. Consequently, this non-pharmacological, cost-effective intervention is a valuable addition to nursing care. Non-pharmacological methods, such as relaxation techniques, are recognized as effective adjunctive treatments in nursing practice.